2020
DOI: 10.1590/0034-761220200137x
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics and communication: an experimental assessment

Abstract: Communication is a key factor in containing a pandemic. Fragmented information may affect people’s perceptions and behaviors, especially in times of governmental miscommunication, potentially jeopardizing efforts aimed at containing the spread of the disease. To test whether and how people have been sensitive to broken information during the COVID-19 pandemic in Brazil, we performed a randomized survey experiment on a sample of 571 respondents. We found that more pessimistic or more optimistic fragmented messa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…So, while it is important to avoid overwhelming people with information, it is also necessary to assess their level of risk perception. Previous studies have shown that perception is related 21 to objective and subjective determinants that impact people’s lives, 22 so it is important to deliver complete information to the population to develop their own perceptions 23 and help them make informed decisions within the crisis. This was also reported in studies conducted during the COVID-19 pandemic, 24 where the role of risk communication to enhance preventive behaviours is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…So, while it is important to avoid overwhelming people with information, it is also necessary to assess their level of risk perception. Previous studies have shown that perception is related 21 to objective and subjective determinants that impact people’s lives, 22 so it is important to deliver complete information to the population to develop their own perceptions 23 and help them make informed decisions within the crisis. This was also reported in studies conducted during the COVID-19 pandemic, 24 where the role of risk communication to enhance preventive behaviours is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Además del uso de redes orientadas a la articulación de actores gubernamentales, detección y monitoreo, gestión de recursos y articulación de pueblos indígenas (Cama et al, 2013;Berardo, 2014;Granda Cantuña et al, 2017;Cardoso y Silva, 2020;. Por último, es importante destacar que la comunicación de riesgos es un factor que influye en el cambio de comportamientos y actitudes frente a distintos riesgos (Vallejos Romero, 2012;Melo y Cabral, 2020;Diniz et al, 2021). Por consiguiente, contribuye al logro de distintas metas (FA=1.4) como la reducción de riesgos de desastres y crisis humanitarias, la generación de resiliencia en la comunidad, y la generación de confianza sobre los gestores (Marín et al, 2020;Pinos y Timbe, 2020;Voos y Marques, 2020;Dada et al, 2021;Zinn, 2021).…”
Section: Factores Clave Para Una Mejor Comunicación De Riesgos Y De C...unclassified